Integrated Pest Management in the Global Arena - Maredia, K. M.; Dakouo, D.; Mota-Sanchez, D.; Ebooks Corporation (Wallingford : CABI, 2003)
A presentation of experiences and successful case studies of integrated pest management (IPM) from developed and developing countries and from major international centres and programmes.
Contenido: Chapter 7. Role of Integrated Pest Management and Sustainable DevelopmentChapter 8. Social and Economic Considerations in the Design and Implementation of Integrated Pest Management in Developing Countries; Chapter 9. Integrated Pest Management Adoption by the Global Community; Chapter 10. Integrated Pest Management in Burkina Faso; Chapter 11. Ghana National Integrated Pest Management Program; Chapte
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: CONTROL BIOLOGICO DE PLAGAS; PLAGAS